IMF Staff papers : Volume 30 No. 4. (IMF Staff Papers; IMF Staff Papers ;, 1983)
This paper focuses on the portfolio-balance model as a framework for addressing unresolved issues about the behavior of exchange rates. The stocks of base money and bonds are determined by the interactions of monetary policies, government budget deficits, and official exchange market interventions. A home-country current account surplus that shifts the residence of private wealth toward the home country will reduce the risk premium on domestic currency, ceteris paribus, if and only if private residents of the home country have a relatively stronger preference for domestic bonds than do private residents of the foreign country. The basic conclusion that has been drawn from the regression analysis is that the risk premiums associated with this particular representation of the portfolio-balance model explain only a small part of the discrepancies between observed percentage changes in exchange rates and forward premiums. Part of the difficulty in obtaining structural estimates of portfolio-demand parameters may reflect deficiencies in specifying the portfolio-balance framework.